2003
DOI: 10.1002/adfm.200304318
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Induced Direct Lithography for Patterning of Carbon with sp3 and sp2 Hybridization

Abstract: A new method of laser‐induced lithography for direct writing of carbon on a glass surface is described, in which deposition occurs from a transparent precursor solution. At the glass–solution interface where the laser spot is focused, a micro‐explosion process takes place, leading to the deposition of pure carbon on the glass surface. Transmission electron microscopy (TEM) analysis shows two distinct co‐existing phases. The dominant one shows a mottled morphology with diffraction typical of cubic (sp3) diamond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…When laser illumination provides heat above a certain threshold, thermally driven reactions that promote material deposition in 2D and 3D can occur. [ 156 ] These methods were referred to as laser‐induced hydrothermal growth, [ 166 ] laser‐assisted hydrothermal method, [ 167 ] laser‐induced direct selective growth, [ 42 ] photothermal chemical liquid growth, [ 168 ] optothermal‐effect‐based mechanism, [ 169 ] laser‐induced solvothermal voxels, [ 170,171 ] direct‐write lithography, [ 172 ] laser‐induced direct lithography, [ 173 ] and in situ laser patterning technique. [ 174 ]…”
Section: Directed Local Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…When laser illumination provides heat above a certain threshold, thermally driven reactions that promote material deposition in 2D and 3D can occur. [ 156 ] These methods were referred to as laser‐induced hydrothermal growth, [ 166 ] laser‐assisted hydrothermal method, [ 167 ] laser‐induced direct selective growth, [ 42 ] photothermal chemical liquid growth, [ 168 ] optothermal‐effect‐based mechanism, [ 169 ] laser‐induced solvothermal voxels, [ 170,171 ] direct‐write lithography, [ 172 ] laser‐induced direct lithography, [ 173 ] and in situ laser patterning technique. [ 174 ]…”
Section: Directed Local Synthesismentioning
confidence: 99%
“…[ 170 ] Other demonstrations utilizing a mixture of precursors include formation of the molecular compound MoS 2 , [ 172 ] as well as AgBr [ 172 ] and Ag‐PVP. [ 172 ] Thermally driven reactions were also shown to decompose organic materials, resulting in patterns that consist of carbon [ 173 ] and Cu@C. [ 174 ] While most of the studies above focused on the formation of micro‐patterns (Figure 8b), some showed that without moving the stage during laser illumination and maintaining low reaction rates, discrete nanowires of ZnO and TiO 2 [ 166,167,169,175 ] can be formed (Figure 8c). Crystalline seeds (such as ZnO) can be pre‐deposited in order to allow faster initiation of the deposition of nanowires.…”
Section: Directed Local Synthesismentioning
confidence: 99%
See 3 more Smart Citations